Detection of Chromosome X;18 Breakpoints and Translocation of the Xq22.3;18q23 Regions Resulting in Variable Fertility Phenotypes - Attila Szvetko; Nicole Martin; Chris Joy; Andrea Hayward; Bob Watson; Andrew Cary; Stephen Withers (Case Reports in Genetics)
We describe a familial pattern of gonosomal-autosomal translocation between the X and 18 chromosomes, balanced and unbalanced forms, in male and female siblings. The proposita was consulted for hypergonadotropic hypogonadism. Karyotype analysis revealed a balanced 46, X, t(X;18)(q22.3;q23) genotype. The sister of the proband presented with oligomenorrhea with irregular menses and possesses an unbalanced form of the translocation 46, X, der(X), t(X;18)(q22.3;q23). The brother of the proband was investigated and was found to possess the balanced form of the same translocation, resulting in disrupted spermatogenesis. Maternal investigation revealed the progenitor karyotype 46, X, t(X;18)(q22.3;q23). Maternal inheritance and various genomic events contributed to the resultant genotypes. Primary infertility was initially diagnosed in all progeny; however, the male individual recently fathered twins. We briefly review the mechanisms associated with X;18 translocations and describe a pattern of inheritance, where breakpoints and translocation of the Xq22.3;18q23 regions have resulted in variable fertility.